Agro-based food production system in Bangladesh: a socio-demographic impact assessment - Karim, A.H.M Zehadul (Medwell Journals, 2011)
Bangladesh faces a daunting challenge to feed its 150 million people of whom at least half of them are living in below food-based poverty-level and another one quarter of them live in extreme poverty. The economy of the country is mostly dependent on agriculture which directly or indirectly has to subsist a huge number of its population, keeping them fully relied on its diversified cropping economy. But due to an unprecedented population growth, the proportion of cultivable land has been squeezing drastically and failing to provide living space and settlements for expanded generations. It eventually puts a tremendous demographic pressure on its agro-based food production system in the rural areas. Based on my ethnographic data collected from the rural areas, researcher have documented genealogically the settlement pattern and food-production system in two villages named Dhononjoypara and Gopalhati in the Northern part of Bangladesh. The study depicts clearly the rate of conversion of the low-lying agricultural land by making a rapid transformation of these into homesteads for settlement. In this context, information have been incorporated since, 1850 to provide ethno-historic data from the revisional settlement surveys of different times and subsequently based on my field-data collected from these specific villages in two phases during 1984-1985 and 2009-2010. Alongside of this, the study also provides information on the over-time population growth and finally concludes with a clear analytical description of the proportionate loss of agricultural land having used clearly the impact on its agro-based food production system in the rural areas of Bangladesh. Finally, the study will also cite examples from other Asian countries to make them aware about it for future.